Challenges of remote consultations: a delayed diagnosis of aortic valve endocarditis complicated by recurrent intracranial events. Issue 2 (28th February 2022) - Demetriades, Polyvios; Ridley, Paul; Yazdani, Farah; Duckett, Simon
Abstract : Embolic events causing stroke and intracranial haemorrhage are among the most catastrophic complications of infective endocarditis (IE). A female patient presented with acute unilateral weakness following a 3-month history of fever, for which she had multiple remote consultations with her general practitioner. A brain MRI confirmed a left sided infarct with haemorrhagic transformation. Blood cultures grew Streptococcus mitis and her cardiac imaging showed an aortic valve vegetation with severe aortic regurgitation. Following 2 weeks of antibiotics she developed a new cerebral haemorrhage associated with a mycotic aneurysm which was treated with two coils. After discussions within the multidisciplinary meeting, she underwent aortic valve replacement 3 weeks later. She made a remarkable recovery and was discharged. Our case highlights the importance of face-to-face clinical review in the post-COVID era. It stresses that the management of patients with infective endocarditis and neurological complications is challenging and requires a multidisciplinary approach.